ENHANCING ENGLISH VOCABULARY THROUGH THE USE OF SNAKE AND LADDER MEDIA FOR 4 TO 6-YEAR-OLD CHILDREN - Murtisari Yemima; Lanny Wijayaningsih; Mozes Kurniawan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2019)
This study aims to improve the English vocabulary of 4 to 6-year-old children at TK Pertiwi 29 Semarang. This research includes classroom action research using snake and ladder media. The research subjects in this study were 20 students from kindergarten group B. Data collection techniques were observation, interview and discussion to classroom teachers and principals, as well as documentation. The research instrument used in this research was observation sheet in the form of checklist. The analysis is using observation data done gradually, then processed into tabulation of observation score and calculated its percentage according to children’s name. The result of this study showed the improvement of percentage from pre-cycle that is 52%, cycle I, which is 59% and 77% in cycle II. Snake and ladder media used in English language learning gradually increase children’s vocabulary.